INFLUENCE OF BRAND IMAGE AND PRODUCT QUALITY ON PURCHASE DECISIONS (MR. BREAD PRODUCT IN INDOMARET STORE) - Jessica Edelina Widjaya; M. Fadhli Nursal (IJESM Indonesian Journal of Economics and Strategic Management, 2023)
This study aims to find out: 1) Does brand image affect purchasing decisions for Mr. Bread 2) Does product quality affect the purchasing decision of Mr. bread. The type of research used in this study is a type of quantitative research. The data collection method in this study was by distributing questionnaires to Mr.'s customers. Bread at Indomaret Pulogadung Industrial Area, East Jakarta. The sample size is taken using the Hair Formula. The Hair formula is used because the population size is not known with certainty. The r value has a value of 0.1796 so it can be concluded that the five statements on the brand image variable are valid. The value of r has a value of 0.1796 so that it can be concluded that the seven statements on the Product Quality variable are declared valid. The value of r has a value of 0.1796, and it can be concluded that the eight statements in the purchasing decision variable are declared valid. So that the Brand Image Variable has a significant influence on purchasing decisions. Product Quality Variables have a significant influence on purchasing decisions.